Hubungan Antara Obesitas Sentral Dengan Kadar Kolesterol Total Pada Penenun Kain Tenun Gringsing Di Desa Tenganan Karangasem - Ni Kadek Lina Winati; I Gusti Ayu Sri Dhyanaputri; I Nyoman Jirna (Jurnal Skala Husada : The Journal of Health, 2022)
ABSTRACTBackground Someone with sedentary life and eat foods with high fat tends had central obesity which is a risk factor for cardiovascular disease. Central obesity can be determined by measurement of waist circumference. Male with waist circumference 90 cm and women with waist circumference 80 cm expressed as central obesity. Objective This research aimed to measure total cholesterol and waist circumference, determine the status of abdominal obesity and analyze the relationship between abdominal obesity with total cholesterol levels of tenun gringsing weavers in Tenganan village of Karangasem Regency. Methode This research use study correlation with saturated sampling technique. Result The results showed that total cholesterol levels of 26 samples, there were 21 samples (80.8%) exceeded normal limits with the highest levels = 291 mg/dl, the lowest levels = 152 mg/dl, and levels mean = 219.62 mg/dl. The result of measurement waist circumference showed from 26 samples, there were 18 respondents with abdominal obesity. From results of Kendall's tau-b statistic showed that there was a very significant association between central obesity with total cholesterol levels of tenun gringsing weavers in Tenganan village of Karangasem Regency (p (0.003) a (0.05)). Conclusion of this study is there are significant association between central obesity with total cholesterol levels of tenun gringsing weavers in Tenganan village of Karangasem Regency.ABSTRAKLatar Belakang Seseorang dengan gaya hidup sedentary dan makan makanan berlemak tinggi cenderung mengalami obesitas sentral yang merupakan faktor risiko penyakit kardiovaskular. Obesitas sentral dapat ditentukan dengan pengukuran lingkar pinggang. Pria dengan lingkar pinggang 90 cm dan wanita dengan lingkar pinggang 80 cm dinyatakan sebagai obesitas sentral. Tujuan Penelitian ini bertujuan untuk mengukur kadar kolesterol total dan lingkar pinggang, mengetahui status obesitas abdominal dan menganalisis hubungan antara obesitas abdominal dengan kadar kolesterol total pada penenun tenun gringsing di desa Tenganan Kabupaten Karangasem. Metode Penelitian ini menggunakan studi korelasi dengan teknik sampling jenuh. Hasil Hasil penelitian menunjukkan kadar kolesterol total dari 26 sampel, terdapat 21 sampel (80,8%) melebihi batas normal dengan kadar tertinggi = 291 mg/dl, kadar terendah = 152 mg/dl, dan kadar rata-rata = 219,62 mg/dl . Hasil pengukuran lingkar pinggang menunjukkan dari 26 sampel terdapat 18 responden yang mengalami obesitas abdominal. Dari hasil statistik tau-b Kendall menunjukkan bahwa terdapat hubungan yang sangat signifikan antara obesitas sentral dengan kadar kolesterol total pada penenun tenun gringsing di Desa Tenganan Kabupaten Karangasem (p (0,003) a (0,05)). Kesimpulan dari penelitian ini adalah terdapat hubungan yang bermakna antara obesitas sentral dengan kadar kolesterol total pada penenun tenun gringsing di desa Tenganan Kabupaten Karangasem.